EVALUATION OF EMPIRICAL ANTIBIOTIC TREATMENT OUTCOMES IN PATIENTS WITH SEVERE COMMUNITY-ACQUIRED PNEUMONIA AT CA MAU GENERAL HOSPITAL IN 2025-2026 (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes of empirical antibiotic therapy and to analyze the impact of antibiotic appropriateness on 28-day mortality in patients with severe community-acquired pneumonia.Subjects and methods: A prospective cohort study was conducted on 120 patients aged ≥ 18 years diagnosed with severe community-acquired pneumonia according to Ministry of Health criteria. Patients were treated at Ca Mau General Hospital from July 2025 to February 2026. The appropriateness of empirical antibiotic regimens was determined based on treatment guidelines and antimicrobial susceptibility results. Patients were followed for 28 days.Results: The mean age was 68.1 ± 14.8 years; 56.7% were male and 64.2% had comorbidities. Appropriate empirical antibiotic therapy was administered in 73.3% of cases. The 28-day mortality rate was 17.5%. Mortality was significantly higher in patients receiving inappropriate empirical antibiotics compared with those receiving appropriate therapy (37.5% vs. 10.2%; p = 0.002). Multivariable analysis showed that inappropriate empirical antibiotic use (OR = 4.1; 95% CI: 1.5-11.2; p < 0.01) and non-susceptible antimicrobial patterns (OR = 2.8; 95% CI: 1.1-7.2; p < 0.05) were independently associated with increased 28-day mortality.Conclusion: Both the appropriateness of empirical antibiotic therapy and non-susceptible antimicrobial patterns are independently associated with 28-day mortality in patients with severe community-acquired pneumonia.
Keywords: Severe community-acquired pneumonia, empirical antibiotic therapy, 28-day mortality.